AN ANALYSIS OF CORPORATE GOVERNANCE EFFICACY IN INDIAN BUSINESS GROUPS TO PROTECT MINORITY SHAREHOLDERS - Danish General (IJRDO - Journal of Business Management, 2026)
Corporate governance has emerged as a critical component of sustainable business management in India, particularly in the context of promoter-driven business groups where ownership concentration is significantly high. Minority shareholders in Indian corporations often face challenges such as information asymmetry, related-party transactions, tunneling of assets, and limited participation in decision-making processes. This research paper examines the efficacy of corporate governance mechanisms in Indian business groups with special emphasis on the protection of minority shareholders. The study evaluates the effectiveness of statutory reforms introduced under the Companies Act, 2013, Securities and Exchange Board of India (SEBI) regulations, Clause 49 of the Listing Agreement, and independent board structures. The paper adopts a doctrinal and analytical research methodology using secondary data from scholarly articles, legal provisions, annual reports, and regulatory frameworks. The findings indicate that although India has adopted internationally accepted governance standards, enforcement deficiencies and concentrated ownership structures continue to undermine minority shareholder protection. The paper further highlights the growing role of shareholder activism, institutional investors, and disclosure norms in improving governance quality. The study concludes that strengthening enforcement mechanisms, enhancing board independence, and improving transparency are essential for safeguarding minority shareholder interests in Indian business groups and ensuring long-term corporate accountability and investor confidence.